Evaluation of Quality of Life and Health Literacy in Women Receiving Infertility Treatment - Menekşe Nazlı Aker; Funda Özdemir (Genel Tıp Dergisi)

(untitled)
Background: Infertility and its treatment can be complex, difficult, and uncomfortable, especially for women. Therefore, it is important to evaluate the quality of life and health literacy of women. Objective: This study was conducted to evaluate the quality of life and health literacy in women receiving infertility treatment and to determine the relationship between the two. Methods: The study, in which a descriptive design was used, was carried out with 186 women who received infertility treatment in Turkey between April 1 and June 30, 2022. Data were collected using a descriptive information form, the Fertility Quality of Life Questionnaire (FertiQoL), and the Turkey Health Literacy Scale-32 (THLS-32). Results: The mean scores of participants were 61.73±16.71 on the total FertiQoL and 36.46±8.45 on the total THLS-32. The level of health literacy was inadequate in 7.5% of women, problematic/limited in 28.5%, adequate in 31.7%, and excellent in 32.3%. There was no significant correlation between FertiQoL and THLS-32 scores (p>.05). Conclusions: In this study, it was determined that the quality of life and health literacy of women who received infertility treatment were not at the desired level.